Antimalarial and neuroprotective effects of ethanolic extracts of the five-flower remedy in an experimental cerebral malaria model - Walaiporn Plirat; Prapaporn Chaniad; Arisara Phuwajaroanpong; Atthaphon Konyanee; Laddawan Lalert; Abdi Wira Septama; Chuchard Punsawad (PLoS ONE, 2025)
Cerebral malaria (CM), a life-threatening consequence of Plasmodium falciparum infection, is associated with a high fatality rate and long-term brain impairment in survivors. Despite advances in malaria treatment, effective therapies to mitigate the severe neurological consequences of CM remain limited. Consequently, novel antimalarial drugs with different mechanisms or neuroprotective advantages are urgently required. This study aimed to explore the potential antimalarial and neuroprotective properties of the five-flower remedy (FFR), a traditional herbal formulation, in experimental cerebral malaria (ECM). Male C57BL/6 mice were induced with Plasmodium berghei ANKA to establish the ECM model. The ethanolic extract of FFR (600 mg/kg) was assessed both as a monotherapy and in combination with artesunate and administered for seven consecutive days starting at the onset of CM symptoms. Parasitemia levels, clinical progression, behavioral changes, and histopathological analysis of brain tissue were analyzed. The results revealed that the ethanolic extract of FFR alone improved outcomes in ECM, while its combination with artesunate significantly reduced parasitemia levels (80%), increased survival rates, reduced neurological deficits, and mitigated brain inflammation and behavioral changes. Histological analysis revealed decreased brain hemorrhage, leukocyte infiltration, and neuronal apoptosis. These promising results suggest that combining artesunate with FFR extract could be a valuable additional treatment for CM. This combination not only improves survival rates but also helps protect the brain by reducing inflammation, neurological damage, and behavioral changes. Further studies are needed to elucidate its drug interaction, mechanisms of action and potential clinical applications.